Decreasing Labor Pain with Counter-Pressure Massage During the First Stage of Labor Active Phase - Wulandari, Mahayanti Arum; Rukmaini, Rukmaini; Choirunissa, Risza (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine whether counter-pressure massage reduces the intensity of labor pain in mothers who give birth in the first stage of the active phase of labor. This research method uses an experimental research type, a pre- and post-test design with a control group design. The research results showed that the average score on the pre-test pain scale reached 7 in both the intervention and control groups. Then, the average pain scale value in the post-test was 5.07 mg/dL in the intervention group and 6.67 mg/dL in the control group. Based on the Independent T-test, it can be concluded that there is a difference in the average level of pain between the intervention group and the control group. In conclusion, Counter-pressure Massage can reduce pain by suppressing pain signals and increasing blood and oxygen flow to all tissues. Midwives need to increase their knowledge about pain relief during childbirth, significantly counter-pressure massage. Keywords: Labor Pain, Counter-Pressure Massage, Active Phase First Stage of Labor